Driver mutation characteristics of phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) in advanced non-small cell lung cancer. (April 2023) - Daher, Sameh; Zer, Alona; Tschernichovsky, Roi; Yacobi, Rinat; Barshack, Iris; Tsabari, Shani; Rottenberg, Yakir; Zick, Aviad; Gottfried, Teodor; Lobachov, Anastasiya; Marom, Edith M.; Urban, Damien; et al.
Highlights: PIK3CA mutated NSCLC patients are older and more likely to have squamous histology. Most PIK3CA mutated patients do not have driver mutation patients' characteristics. PIK3CA mutation may be targetable in patients who lack other targetable alterations. A never smoker PIK3CA mutated patient responded to PI3Ka-selective inhibitor. Abstract: Objectives: The identification and targeting of actionable genomic alterations (AGA) have revolutionized the treatment of cancer in general and mostly for non-small cell lung cancer (NSCLC). We investigated whether in NSCLC patients PIK3CA mutations are actionable. Materials and Methods: Chart review was performed of advanced NSCLC patients. PIK3CA mutated patients were analyzed as two groups: Group A: without any non- PIK3CA established AGA; Group B: with coexisting AGA. Group A was compared to a cohort of non- PIK3CA patients (group C), using t -test and chi-square. To evaluate the impact of PIK3CA mutation on outcome, we compared Group A survival to age/sex/histology matched cohort of non- PIK3CA mutated patients (group D) by Kaplan-Meier method. A patient with a PIK3CA mutation was treated with a PI3Ka-isoform selective inhibitor BYL719 (Alpelisib). Results: Of a cohort of 1377 patients, 57 are PIK3CA mutated (4.1%). Group A: n-22, group B: n-35. Group A median age is 76 years, 16 (72.7%) men, 10 (45.5%) squamous, 4 (18.2%) never smokers. Two never-smoker female adenocarcinoma patients had solitary PIK3CA mutation. One of them was treated with a PI3Ka-isoform selective inhibitor BYL719 (Alpelisib), with rapid clinical and partial radiological improvement. Group B, compared with Group A, included younger patients (p = 0.030), more females (p = 0.028) and more adenocarcinoma cases (p < 0.001). Compared to group C, group A patients were older (p = 0.030) and had more squamous histology (p = 0.011). Conclusion: In a small minority of NSCLC patients with PIK3CA mutation there are no additional AGA. PIK3CA mutations may be actionable in these cases.